Improving Employee Health: Evaluation of a Worksite Lifestyle Change Program to Decrease Risk Factors for Diabetes and Cardiovascular Disease. Issue 3 (March 2015) - Kramer, M. Kaye; Molenaar, Donald M.; Arena, Vincent C.; Venditti, Elizabeth M.; Meehan, Rebecca J.; Miller, Rachel G.; Vanderwood, Karl K.; Eaglehouse, Yvonne; Kriska, Andrea M.
Abstract : Objective: To determine whether an evidence-based, behavioral lifestyle intervention program delivered at a worksite setting is effective in improving type 2 diabetes and cardiovascular disease risk factors. Methods: A randomized 6-month delayed control design was utilized, with two thirds of the participants assigned to begin intervention immediately, and one third beginning 6 months later. The year-long program (weekly for 3 months transitioning to monthly) focused on weight loss and increasing physical activity. Results: The immediate intervention group had greater mean weight loss (−10.4 lb, 5.1%, vs −2.3 lb, 1%; P = 0.0001) than the delayed control group at 6 months and relatively greater improvements in activity, HbA1c, and other risk factors. The delayed group experienced similar improvements after completing the intervention program. Conclusions: A worksite behavioral lifestyle intervention is feasible and effective in significantly improving risk factors for type 2 diabetes and cardiovascular disease.